A descriptive phenomenological approach to perception of affective quality in design inspiration. (January 2022) - Rangarajan, Vimalkrishnan; Onkar, Prasad S.; De Kruiff and Deirdre Barron, Alison
Abstract : The psychological term affective quality denotes the ability of objects to change how individuals feel when they encounter those objects. In design research, the affective qualities of inspirational materials and the perception of such affective qualities have been studied, mainly from a positivist standpoint. This involves experimental methodologies and tools like rating scales which imply objective measurements of perception of affective qualities to establish cause-effect relationships. However, affective quality is enmeshed in cultural and contextual frameworks. This implies that there can be subjective perceptions of affective quality that demand more descriptive research. This paper contextualises a descriptive phenomeological approach to study designers' subjective perceptions of affective qualities of inspirational material. This approach fosters methodological diversity and theory-building research in design. Highlights: Affective quality is the ability of various objects to influence how people 'feel'. Designers perceive affective qualities of various inspirational materials. Such perceptions are subjective, enmeshed in contextual and cultural frameworks. To capture such rich subjective perceptions, descriptive phenomenology is proposed. This fosters methodological diversity and theory-building research in design.